2015
DOI: 10.5751/es-07857-200402
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of multiple goods, ecosystem services, and property rights in large social-ecological marine protected areas

Abstract: ABSTRACT. Protected areas are a cornerstone of biodiversity conservation, and increasingly, conservation science is integrating ecological and social considerations in park management. Indeed, both social and ecological factors need to be considered to understand processes that lead to changes in environmental conditions. Here, we use a social-ecological systems lens to examine changes in governance through time in an extensive regional protected area network, the Great Barrier Reef Marine Park. We studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In this sense, socioecological system (SES) debates should be further investigated (e.g. Ostrom 2009;McGinnis and Ostrom 2014;Ban et al 2015;Partelow and Winkler 2016) if policy or practical agendas for solving underuse problems are to be seriously considered. Second, the theme of local peculiarities should have greater recognition and be subject to more exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, socioecological system (SES) debates should be further investigated (e.g. Ostrom 2009;McGinnis and Ostrom 2014;Ban et al 2015;Partelow and Winkler 2016) if policy or practical agendas for solving underuse problems are to be seriously considered. Second, the theme of local peculiarities should have greater recognition and be subject to more exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Ban et al (2015) demonstrate how the coconsideration of multiple ES in an analysis structured with the SESF can help better understand complexities in a large-scale marine system. Grêt-Regamey et al (2014) suggest incorporating Ostrom's tiered structure of multilevel interactions to map ES assessments.…”
Section: Overviewmentioning
confidence: 99%
“…Lacroix and Richards (2015) applied the design principles to the carbon tax in British Columbia, Canada, and found that their assessment added insights beyond those provided by existing policy analyses. Ban et al (2015b) used a SES lens to examine changes in governance through time in the Great Barrier Reef Marine Park, Australia, assessing changes in property rights and multiple goods and ecosystems services.…”
Section: Summary Of the Articlesmentioning
confidence: 99%
“…This special feature thus had two objectives: (1) provide examples and support for teachers committed to engaging students with ideas around complex SESs (Ban et al 2015a, Cox 2015, and (2) provide a set of case studies led by or involving students that examines large case studies (> 10,000 km²; Ban et al 2015b, Lacroix and Richards 2015, Lancaster et al 2015, Taggart-Hodge and Schoon 2016, Tyson 2017, Villamayor-Tomas et al 2016). …”
Section: Introductionmentioning
confidence: 99%